Pertanggungjawaban Hukum Kepada Lender dari Konsep Bisnis Inventory Financing serta Penyelesaian Sengketa - Riyantika, Annisa; Putra, David Aprizon (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2024)
The Inventory Financing business model is starting to develop in the peer-to-peer lending system in Indonesia. The development factor from peer-to-peer lending to Inventory Financing is the existence of collateral that is still controlled by the borrower (debtor). This research examines the legal responsibility of the lender in Inventory Financing, and dispute resolution when one party is negligent in performing its obligations. This article aims to find Inventory Financing arrangements that protect lenders and dispute resolution methods of Inventory Financing. This research uses a normative juridical method (desk research) using secondary data, namely laws and regulations and theories of contract law, development law, and legal protection. The findings in this study are that Inventory Financing is still not regulated, so it has the potential to cause disputes in its implementation. Another finding is that the method of resolving inventory financing disputes can be done through judicial and non-judicial institutions (Alternative Dispute Resolution Institutions). Alternative Dispute Resolution Institutions can be ideal because they can resolve problems quickly, easily, and cheaply.Keywords: Alternative Dispute Resolution Institution, Financial Services Authority, Peer to Peer Lending